Evaluation of maize weevils Sitophilus zeamais Motschulsky infestation on seven varieties of maize. (October 2015) - Suleiman, R.; Rosentrater, K.A.; Bern, C.J.
Abstract: Sitophilus zeamais (Motschulsky), the maize weevil, is a serious pest of economic importance in stored products in tropical and subtropical countries; infestation often starts in the field, but serious damage is done during maize storage. This study evaluated S. zeamais infestation on seven varieties of maize. Seven commercial maize varieties (white dent, yellow dent, orange flint, Indian flint, white popcorn, yellow popcorn and sweet corn), two temperature conditions (10 and 27 °C) and three storage times (30, 60, and 90 d) were used. The moisture contents of all maize samples were adjusted to 15.5 ± 0.5% (wet basis) prior to initiating storage trials. Numbers of live weevils, – seed damage, weight loss, and weight of powder produced were assessed at the end of each storage time. As expected, severe damage was observed at 27 °C and 90 d for all maize varieties. Exponential growth rates of S. zeamais were observed in almost all maize varieties. Among seven varieties evaluated, orange flint corn, yellow and white popcorn show resistance to S. zeamais . Nevertheless, sweet and dent corn were most susceptible to S. zeamais -infestation - Higher numbers of live S. zeamais were observed on Indian flint corn, sweet corn and yellow dent corn. Consequently, there was higher seed weight damaged and weight loss. Further, seed damaged, percentage seed weight loss and weight of powder produced was significantly and positive correlated with number of live S. zeamais (r = 0.91, P < 0.05), (r = 0.88, P < 0.05), and (r = 0.89, P < 0.05) respectively. Thus, some varieties of flint corn and popcorn can be considered as potential maize varieties to be used to reduce postharvest loss of maize in tropical countries due to natural resistance to S. zeamais infestation. Highlights: Exponential growth of S. zeamais was observed in all varieties except yellow popcorn. The highest weevil populations were observed in Indian flint corn, sweet corn and yellow dent corn. Maize variety, temperature and time had significant effects on all infestation and maize quality parameters. Among the seven varieties, orange flint corn, yellow and white popcorn show resistance to S. zeamais. The higher percentage of seed weight loss was observed in yellow dent corn at 27 °C and 90 days of storage.